Forest Health in Italy: Learning From the Xylella Incursion - Vettraino, Anna Maria; Santini, Alberto (Frontiers in Forests and Global Change, 2021)
Italy has an increasing part of its territory covered by forest, particularly prone to invasion by invasive forest pathogens (IFPs) owing to the presence of many different habitats and climates. To be effective, any preventive or management tools to prevent the arrival and establishment of IFPs must be included in the framework of phytosanitary legislation. The European Union has an open-door phytosanitary system meaning that any consignment that is not specifically regulated can enter. Increasing evidence of the limitations and subsequent gaps in biosecurity with the current system. Learning from the recent outbreak of Xylella fastidiosa, we provide comments and suggestions to fill the gaps and improve the phytosanitary system in Italy.